Regional Development Policy Through Housing Programs for Poor Communities in Pekanbaru City - Zaili Rusli; Adianto Adianto (Indonesian Association for Public Administration (IAPA), 2019)
Pekanbaru City as one of the cities in Indonesia that is experiencing rapid development and growth in the development of various fields. This reality shows that the City of Pekanbaru must be ready to face all forms of population problems that will arise, one of which is the housing needs of the urban poor. The purpose of this study is to comprehensively analyze regional development policies through housing programs for the community in Pekanbaru City. This type of research is qualitative research with a case study approach that uses key informants and supplementary informants as a source of information. Data collection is done through observation and interviews, then after the data collected will be used triangulation methods with data sources and then analyzed and interpreted by providing conclusions. The results of the study found that the form of housing policy for the people in Pekanbaru City consisted of the livable housing program (RLH), the city program and the house renovation program. Furthermore, the implementation of housing policy for the people in Pekanbaru City has run quite well. This means that every urban poor community is indeed a priority for the Pekanbaru City Government as a target group that must accept programs in the housing sector. However, the constraints of housing quota intended for the poor have not been able to fully meet the existing needs, so the Pekanbaru City Government has to make a turn system so that all urban poor communities can receive housing programs provided.